A Nonlinear Controller for Single Phase Inverter with Uncertain Output LC Filter Feeding A Nonlinear Load - Turker, Turker; Bakan, Faruk (IEEE, 2018)
A nonlinear controller is presented for a single phase inverter with an uncertain LC filter at the output. Nonlinear load condition is also considered and the designed controller is modified accordingly. Backstepping scheme is applied for two loop structure of the system while uncertainties are handled via adaptation mechanisms involved in the controller. Proposed controller is compared with two loop PI controller by means of numerical simulations and its advantageous response is demonstrated.
Keywords: nonlinear control; single phase inverter; UPS application; Automation & Control Systems; Computer Science; Engineering